Acid–base behavior, electrochemical properties and DFT study of redox non-innocent phenol–imidazole ligands and their Cu complexes. (15th October 2015) - Parween, Arfa; Mandal, Tarun Kanti; Guillot, Régis; Naskar, Subhendu
Graphical abstract: Three redox active phenol–imidazole ligands and their Cu complexes have been reported here. The imidazole group is covalently linked to the ortho position of phenolic-OH. p K a values of the ligands have been determined UV–Vis spectrophotometrically. Imidazolium proton in the ligands is more acidic than the imidazole itself, whereas the phenolic-OH is slightly less acidic than the phenol. Oxidation potential for the phenolic-OH to the phenoxyl radical is less than the phenol itself as observed from the cyclic voltammetry. The oxidation process is highly pH dependent ad E 0 value decreases with increase in pH. This low E 0 values and different p K values are due to presence of imidazole ring to the ortho position of phenol, the former acting as intramolecular base. This type of arrangement can form strong hydrogen bonding which stabilise the conjugate bases or the oxidized phenoxyl radical. Metal complexes have almost similar or even less E 0 value than ligand. This may be due to Cu assisted stabilization of the phenoxyl radicals. Abstract: Three Cu complexes (1, 2, 3 ) with N, O donor ligands having imidazole–phenol moieties 2-(4, 5-diphenyl-1H-imidazol-2-yl)phenol (L 1 H ), 4-bromo 2-(4, 5-diphenyl-1H-imidazol-2-yl)phenol (L 2 H ) and 1-(4, 5-diphenyl-1H-imidazol-2-yl)naphthalene-2-ol (L 3 H ) have been synthesized and characterized by spectroscopic techniques. Molecular structure of one Cu complex (2 ) has been determined by X-ray crystallography.2 ·DMF crystallises in monoclinic P 21 / c space group with an exactly intermediate geometry between tetrahedral and square planar ( τ 4 = 0.5319). The p K a values of the ligands were determined by UV–Vis spectrophotometric titration. The imidazole–phenol ligand exhibit a high sensitivity towards the pH of the solution. p K a of the imidazolium cation is ∼4.1, whereas p K a for the phenolic deprotonation is in the range 10–10.7. Electronic spectra of the complexes consist of a phenoxide to Cu II LMCT in the region (490–500 nm) and a d–d transition in the range (620–716 nm). All the ligands and the complexes exhibit one ligand based oxidation: phenol/phenoxyl radical or phenolate/phenoxyl radical. pH dependent electrochemical study shows the oxidation process is highly pH sensitive. Potential for this oxidation is close to that observed in Galactose oxidase.